2017
DOI: 10.1002/1873-3468.12572
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure to small molecules allows induction of mouse embryonic fibroblasts into neural crest‐like precursors

Abstract: In this study, we propose a novel method for inducing neuronal cells by briefly exposing them to small‐molecule cocktails in a step‐by‐step manner. Global gene expression analysis with immunohistochemical staining and calcium flux assays reveal the generation of neurons from mouse embryonic fibroblasts. In addition, time‐lapse imaging of neural precursor‐specific enhancer expression and global gene expression analyses show that the neurons are generated by passing through a neural crest‐like precursor stage. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…Based on our previous study, we selected the following four chemical patterns (cp1–4), and examined their effects on human ADSCs ( Fig 1A ); cp1: the same combination as we previously reported [ 14 ]; cp2: adding DZNep, a histone methyltransferase inhibitor [ 17 ], and EPZ, a selective inhibitor of DOT1L (a protein methyltransferase catalyzing the methylation of H3K4 [ 18 ]) to cp1; cp3: adding ISX9, inducer of neuronal differentiation [ 19 ], to cp1; and cp4: excluding VPA and Tranyl from cp3. Subsequently, NGFR expression was analyzed via immunofluorescence measurement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previous study, we selected the following four chemical patterns (cp1–4), and examined their effects on human ADSCs ( Fig 1A ); cp1: the same combination as we previously reported [ 14 ]; cp2: adding DZNep, a histone methyltransferase inhibitor [ 17 ], and EPZ, a selective inhibitor of DOT1L (a protein methyltransferase catalyzing the methylation of H3K4 [ 18 ]) to cp1; cp3: adding ISX9, inducer of neuronal differentiation [ 19 ], to cp1; and cp4: excluding VPA and Tranyl from cp3. Subsequently, NGFR expression was analyzed via immunofluorescence measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical staining analysis was performed as previously reported [ 5 , 14 ]. Briefly, the samples were fixed with 3.7% formaldehyde (FUJIFILM Wako Pure Chemical Industries) and permeabilized with PBS containing 0.2% Tween-20 (FUJIFILM Wako Pure Chemical Industries).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells resemble primary NSCs in terms of their long-term self-renewal and tripotent differentiation abilities. Takayama et al 39 also developed a small-molecule cocktail composed of VPA, Forskolin (an adenylyl cyclase activator), Parnate, CHIR99021, Repsox, Dorsomorphin (a selective inhibitor of BMP signaling) and SB431542 (a selective inhibitor of TGF- β receptor I, such as ALK4 and ALK7) to induce neural crest-like precursors from mouse embryonic fibroblasts. Zheng et al 40 showed that a combination of A83-01, Purmorphamine (a smoothened receptor agonist), VPA and Thiazovivin (a selective Rho-associated protein kinase inhibitor) can directly lead to the generation of ciNSCs.…”
Section: Strategies For the Isolation And Generation Of Nscsmentioning
confidence: 99%